The Association Between Goodwill Impairment and Discretionary Accruals: Portuguese Evidence - Alves, Sandra (JABM JOURNAL of ACCOUNTING - BUSINESS & MANAGEMENT, 2013)
Portuguese listed firms (as well all EU companies) have been required to use IFRS and consequently IFRS 3 Business Combinations and IAS 36 Impairments of Assets since 2005. On adopting IFRS 3 goodwill is no longer amortised but is subject to an annual impairment test in accordance with IAS 36. Previous studies suggest that the impairment of goodwill decision is influenced by managers (e.g. Beatty and Weber, 2006; Jahmani et al., 2010; Van de Poel et al., 2009), which may exercise discretion in determining the recoverable value of goodwill. Therefore, this paper investigates whether Portuguese listed companies use goodwill impairment loss to manage earnings. Using a sample of 33 Euro next Lisbon non-financial firms over a period of 6 years, from 2005 through 2010, we find that the goodwill impairment amount is significantly positively related to earnings management, suggesting that IAS 36 provides managers with discretion for goodwill write-off.